SOCIAL SUPPORT FOR FAMILIES AS A CASE MANAGEMENT TECHNOLOGY - Василюк, Тамара; Лисоконь, Ілля (SWorldJournal, 2024)
Socio-economic development in Ukraine is uneven. There are many reasons for such fluctuations, but the main ones include financial instability at the global level, a high level of corruption, a low permanent deficit of the state budget, which in turn doe